Macrophage–Neisseria gonorrhoeae Interactions: A Better Understanding of Pathogen Mechanisms of Immunomodulation - Escobar, Alejandro; Rodas, Paula I.; Acuña-Castillo, Claudio (Frontiers in Immunology, 2018)
Neisseria gonorrhoeae is a significant health problem worldwide due to multi-drug resistance issues and absence of an effective vaccine. Patients infected with N. gonorrhoeae have not shown a better immune response in successive infections. This might be explained by the fact that N. gonorrhoeae possesses several mechanisms to evade the innate and adaptative immune responses at different levels. Macrophages are a key cellular component in the innate immune response against microorganisms. The current information suggests that gonococcus can hijack the host response by mechanisms that involve the control of macrophages activity. In this mini-review, we intend to condense the recent knowledge on the macrophage–N. gonorrhoeae interactions with a focus on strategies developed by gonococcus to evade or to exploit immune response to establish a successful infection. Finally, we discuss the opportunities and challenges of therapeutics for controlling immune manipulation by Neisseria gonorrhoeae.